Mind the Gap: The State of Girls’ Education in Crisis and Conflict - Inter-agency Network for Education in Emergencies (INEE, 2021)

Distance Learning during COVID-19 - Inter-Agency Network for Education in Emergencies (2020)
The third webinar of the INEE COVID-19 webinar series focused on providing distance learning in low-resource and low tech environments. The webinar highlighted the challenges currently facing EiE practitioners in the face of the school closures and restricted movement associated with COVID-19. EiE actors shared guidance and recommendations for continuing learning along with practical examples. More information about this webinar and INEE's COVID-19 response can be found on the INEE website: https://inee.org/collections/coronavi...

A Guidance Note for Teacher Wellbeing in Emergency Settings - Inter-agency Network for Education in Emergencies (INEE, 2022)

Teacher Wellbeing Resources Mapping & Gap Analysis - Inter-Agency Network for Education in Emergencies (2021)

Promising Practices in Teacher Professional Development - Inter-Agency Network for Education in Emergencies (Teachers in Crisis Context, 2022)

Education technology | INEE - Inter-Agency Network for Education in Emergencies
Keywords: ⛔ No INSPIRE recid found

Minimum Standards Handbook - Inter-Agency Network for Education in Emergencies (2012)

Minimum Standards for Education: Preparedness, Response, Recovery - Inter-Agency Network for Education in Emergencies (Inter-agency Network for Education in Emergencies (INEE), 2010)
The Handbook is designed to give governments and humanitarian workers the tools that they need to address both local and global goals. It is the first step toward ensuring that education initiatives in emergency situations provide a solid and sound basis for post-conflict and disaster reconstruction. The INEE Minimum Standards express a commitment that all individuals – children, youth, and adults – have a right to education during emergencies and fragile contexts. They echo the core beliefs of the Sphere Project: that all possible steps should be taken to alleviate human suffering arising out of calamity and conflict, and that people affected by disaster have a right to life with dignity.

Landscape Review: Education in Conflict and Crisis - How Can Technology Make a Difference? - Inter-agency Network for Education in Emergencies (INEE). (2016)

EiE Glossary: Education in Emergencies - Inter-agency Network for Education in Emergencies (INEE) (INEE, 2024)

Disability-Inclusive EiE Resources Mapping and Gap Analysis - Inter-agency Network for Education in Emergencies (INEE) (INEE, 2023)

Disability-Inclusive Education in Emergencies: Key concepts, approaches, and principles for practice - Inter-agency Network for Education in Emergencies (INEE) (INEE, 2023)

Distance Education in Emergencies - Inter-agency Network for Education in Emergencies (INEE) (2022)

Refugee education during COVID-19: Crisis and Opportunity - Inter-Agency Network for Education in Emergencies (INEE) (2020)

Coronavirus (COVID-19) Resources | INEE - Inter-agency Network for Education in Emergencies (INEE). (2020)

Rapid Evidence Summary on Mass Communication | - Inter-agency Network for Education in Emergencies (INEE). (2020)

Technical Note: Education during the COVID-19 Pandemic. - Inter-agency Network for Education in Emergencies (INEE). (2020)
We are thrilled to share a new INEE Technical Note on Education during the COVID-19 Pandemic.

Minimum Standards for Education: Preparedness, Response, Recovery - Inter-agency Network for Education in Emergencies (INEE) (2024)

Checklist for Information and Communications Technologies (ICT) Interventions to Support Education in Crisis and Conflict Settings - Inter-agency Network for Education in Emergencies (INEE); USAID (2018)

Accelerated Education in the Democratic Republic of Congo, South Sudan, Tanzania and Uganda - Accelerated Education Working Group (AEWG); Inter Agency Network for Education in Emergencies (INEE) (2022)